Method for producing oxynitride, method for producing photocatalyst, and method for producing hydrogen
Patent Information
- Application Number
- JP2022141198
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-08
- Filing Date
- 2022-09-06
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-09-06
AI Technical Summary
【0007】 本発明によれば、新規の酸窒化物の製造方法が提供される。また、本発明によれば、光触媒の製造方法、及び、光触媒を用いた水素の製造方法が提供される。
Smart Images

Figure 0007943623000001 
Figure 0007943623000002 
Figure 0007943623000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to a method for producing oxynitride, a method for producing a photocatalyst, and a method for producing hydrogen. [Background technology]
[0002] In recent years, methods for producing hydrogen by splitting water using sunlight have been investigated. For example, Patent Document 1 discloses a photocatalyst for photocatalytic water splitting reactions, in which an oxidation reaction co-catalyst and a reduction reaction co-catalyst are supported on a photosemiconductor (for example, Patent Document 1).
[0003] As photocatalysts, oxynitrides, which are solid solutions of metal nitrides and metal oxides, are known to be used as photocatalysts, and various methods for producing them have been investigated. For example, Patent Document 2 discloses a method in which Ga2O3 powder and ZnO powder are suspended in a gas phase containing nitrogen gas, ammonia gas, and hydrocarbon gas, and heated to 600-1000°C. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2011-173102 [Patent Document 2] Japanese Patent Publication No. 2006-116415 [Overview of the project] [Problems that the invention aims to solve]
[0005] The present invention aims to provide a novel method for producing oxynitrides. Furthermore, the present invention aims to provide a method for producing photocatalysts and a method for producing hydrogen using photocatalysts. [Means for solving the problem]
[0006] The present invention relates, for example, to (1) to (17) below. (1) A method for producing oxynitride, comprising a reaction step of heating a mixture of a metal oxide (A), a metal nitride (B), and a metal halide (C) in a closed system. (2) The method for producing the metal oxide (A) according to (1), wherein the metal oxide (A) contains at least one metal element selected from the group consisting of Zn, Al, Ga, In, Ge, and Sn. (3) The method for producing a metal oxide according to (2), wherein the metal oxide (A) comprises a metal oxide (A-1) containing at least one metal element selected from the group consisting of Al, Ga, In, Ge, and Sn. (4) The manufacturing method according to (3), wherein the metal oxide (A) further comprises a metal oxide (A-2) containing Zn. (5) The manufacturing method according to any one of (1) to (4), wherein the metal nitride (B) contains at least one metal element selected from the group consisting of Zn, Al, Ga, In, Ge, Sn, Li, Na, Mg, Ca, Sr, Ba, and La. (6) The manufacturing method according to any one of (1) to (5), wherein the metal nitride (B) is a compound (B') containing a metal element, a nitrogen atom, and a halogen atom. (7) The method for producing the compound (B') described in (6), wherein the compound (B') is Zn2NX (where X represents a halogen atom). (8) The manufacturing method according to any one of (1) to (7), wherein the metal halide (C) contains at least one metal element selected from the group consisting of Zn, Al, Ga, In, Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, and La. (9) A method for producing an oxynitride according to any one of (1) to (8), wherein the oxynitride is a solid solution of a metal nitride (i) and a metal oxide (ii). (10) The manufacturing method according to (9), wherein at least one of the metal oxide (A) and the metal nitride (B) contains Zn, and the metal oxide (ii) contains ZnO. (11) At least one of the aforementioned metal oxide (A) and the aforementioned metal nitride (B) contains at least one metal element (α) selected from the group consisting of Al, Ga, In, Ge and Sn, The production method according to (9) or (10), wherein the aforementioned metal nitride (i) contains the aforementioned metal element (α). (12) The production method according to any one of claims (1) to (11), further comprising a firing step of firing the oxynitride obtained in the aforementioned reaction step. (13) The production method according to (12), wherein the aforementioned firing step includes firing in an oxygen-containing atmosphere. (14) The production method according to (12) or (13), wherein the aforementioned firing step includes firing in an ammonia-containing atmosphere. (15) The production method according to any one of (12) to (14), wherein the aforementioned firing step includes firing in an inert gas atmosphere. (16) A method for producing a photocatalyst, comprising the step of supporting an oxidation reaction co-catalyst and a reduction reaction co-catalyst on the oxynitride produced by the production method according to any one of (1) to (15), to obtain the photocatalyst. (17) A method for producing hydrogen, comprising the step of bringing the photocatalyst produced by the production method according to (16) into contact with water to decompose the aforementioned water. [Advantageous Effects of the Invention]
[0007] According to the present invention, a novel method for producing an oxynitride is provided. Further, according to the present invention, a method for producing a photocatalyst and a method for producing hydrogen using the photocatalyst are provided. [Brief Description of the Drawings]
[0008] [Figure 1]Figure 1(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Example A-1, Comparative Example X-1, Comparative Example X-2, Comparative Example X-3, and Comparative Example X-4, and Figure 1(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Example A-1, Comparative Example X-1, Comparative Example X-2, Comparative Example X-3, and Comparative Example X-4. [Figure 2] Figure 2(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples A-1, A-2, and A-3, and Figure 2(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Examples A-1, A-2, and A-3. [Figure 3] Figure 3(a) shows the FE-SEM image of the oxynitride obtained in Example A-1, and Figure 3(b) shows the FE-SEM image of the oxynitride obtained in Example A-2. [Figure 4] Figure 4 shows the evaluation results of the hydrogen generation activity of the photocatalysts obtained in Examples B-1 and B-2. [Figure 5] Figure 5(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Example A-2, Example C-1, and Comparative Example X-5, and Figure 5(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Example A-2, Example C-1, and Comparative Example X-5. [Figure 6] Figure 6 shows the evaluation of the hydrogen generation activity of the photocatalysts obtained in Example B-2, Example C-1, and Comparative Example X-5. [Figure 7] Figure 7(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples A-1 and D-1, and Figure 7(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Examples A-1 and D-1. [Figure 8] Figure 8(a) shows the FE-SEM image of the oxynitride obtained in Example A-1, and Figure 8(b) shows the FE-SEM image of the oxynitride obtained in Example D-1. [Figure 9]Figure 9(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples A-1, E-1, and E-2, and Figure 9(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Examples A-1, E-1, and E-2. [Figure 10] Figure 10 shows the evaluation results of the water-splitting activity of the photocatalysts obtained in Examples E-1 and E-2. [Figure 11] Figure 11(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples A-1, F-1, F-2, and F-3, and Figure 11(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Examples A-1, F-1, F-2, and F-3. [Figure 12] Figure 12(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples F-1, G-1, G-2, and G-3, and Figure 12(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Examples F-1, G-1, G-2, and G-3. [Figure 13] Figure 13(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Example H-1, Comparative Example Y-1, and Comparative Example Y-2, and Figure 13(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Example H-1, Comparative Example Y-1, and Comparative Example Y-2. [Figure 14] Figure 14(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples H-1, H-2, H-3, and H-4, and Figure 14(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Examples H-1, H-2, H-3, H-4, and Comparative Example Y-2. [Figure 15] Figure 15(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples A-1, J-1, and J-2, and Figure 15(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Examples J-1 and J-2. [Figure 16] Figure 16 shows the evaluation results of the water-splitting activity of the photocatalysts obtained in Examples K-1 and K-2. [Figure 17] Figure 17 shows the evaluation results of the water-splitting activity of the photocatalysts obtained in Examples L-1 and L-2. [Figure 18] Figure 18(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples M-1 and M-2, and Figure 18(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Examples M-1 and M-2. [Figure 19] Figure 19 shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples N-1 and N-2. [Figure 20] Figure 20 shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples O-1, O-2, and O-3. [Figure 21] Figure 21 shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples O-4 to O-7. [Modes for carrying out the invention]
[0009] Preferred embodiments of the present invention will be described in detail below.
[0010] (Method for producing oxynitrides) The method for producing oxynitrides in this embodiment comprises a reaction step of heating a mixture of a metal oxide (A), a metal nitride (B), and a metal halide (C) in a closed system. Such a production method allows for the efficient production of oxynitrides.
[0011] In this embodiment, the oxynitride contains a metal element, an oxygen atom, and a nitrogen atom. The oxynitride may contain a metal nitride (i) and a metal oxide (ii), and may be a solid solution of the metal nitride (i) and the metal oxide (ii). According to this embodiment, there is a tendency to obtain an oxynitride with a large amount of solid solution of metal oxide (ii).
[0012] In the manufacturing method of this embodiment, for example, metal nitride (B) may serve as a nitrogen source, and metal oxide (A) may be nitrided to form an oxynitride containing metal nitride (i) and metal oxide (ii). That is, in this embodiment, metal nitride (i) may contain the same metal elements as metal oxide (A), and metal oxide (ii) may contain the same metal elements as metal nitride (B).
[0013] In the manufacturing method of this embodiment, the metal halide (C) is thought to melt upon heating during the reaction process and function as a dispersion medium for dispersing the solid powder metal oxide (A) and metal nitride (B). In other words, the presence of the metal halide (C) is thought to allow the reaction between the metal oxide (A) and metal nitride (B) to proceed efficiently and uniformly. However, if the reaction process is carried out in the absence of the metal halide, the nitridation of the metal oxide may not proceed sufficiently, and a composite oxide may be formed.
[0014] In conventional manufacturing methods, open systems can lead to uneven composition due to the volatilization of metal components (e.g., metal oxides), and it can be difficult to produce oxynitrides with a high solid solubility of metal oxides. Even in closed systems, using ammonium chloride as a nitrogen source can generate large amounts of hydrogen, increasing internal pressure and posing a risk of explosion upon opening, making mass production difficult. Furthermore, the generated hydrogen can reduce and decompose the oxynitride, resulting in the inclusion of metal components as impurities. In this embodiment, the volatilization of metal components can be suppressed, resulting in a more uniform composition of the obtained oxynitride, and making it easier to obtain oxynitrides with a high solid solubility of metal oxides. Moreover, since there is no hydrogen generation in the system, this method offers superior safety, and allows for the production of high-purity oxynitrides composed of easily reducible metal elements.
[0015] In the manufacturing method of this embodiment, the metal oxide (A) and the metal nitride (B) may be appropriately selected according to the metal elements present in the target oxynitride (the metal elements present in the metal nitride (i) and the metal oxide (ii)).
[0016] For example, if the metal nitride (i) in the oxynitride contains at least one metal element (α) selected from the group consisting of Al, Ga, In, Ge, and Sn, then at least one of the metal oxide (A) and the metal nitride (B) may contain the metal element (α).
[0017] Furthermore, for example, if the metal oxide (ii) in the oxynitride contains Zn, then at least one of the metal oxide (A) and the metal nitride (B) may contain Zn.
[0018] Examples of oxynitrides include AlN:ZnO, GaN:ZnO, InN:ZnO, ZnGeN2:ZnO, ZnSnN2:ZnO, and their solid solutions. The notation X:Y for oxynitrides refers to a solid solution of X and Y. For example, AlN:ZnO indicates a solid solution of AlN and ZnO.
[0019] The metal oxide (A) preferably contains at least one metal element selected from the group consisting of Zn, Al, Ga, In, Ge, and Sn.
[0020] Metal oxide (A) may include metal oxide (A-1) containing at least one metal element selected from the group consisting of Al, Ga, In, Ge, and Sn. Preferably, metal oxide (A-1) contains at least one metal element selected from the group consisting of Ga, Ge, and In, and more preferably, at least one metal element selected from the group consisting of Ga and Ge.
[0021] The metal oxide (A-1) may be at least one selected from the group consisting of Al2O3, Ga2O3, ZnGa2O4, In2O3, GeO2, Zn2GeO4, and SnO2, preferably at least one selected from the group consisting of Al2O3, Ga2O3, In2O3, GeO2, and SnO2, more preferably at least one selected from the group consisting of Ga2O3, In2O3, and GeO2, and even more preferably at least one selected from the group consisting of Ga2O3 and GeO2.
[0022] Furthermore, metal oxide (A) may also contain metal oxide (A-2) containing Zn, along with metal oxide (A-1) (however, metal oxide (A-2) is different from metal oxide (A-1).
[0023] Examples of metal oxides (A-2) include ZnO, ZnGa2O4, and Zn2GeO4. For example, metal oxide (A-2) may be ZnO.
[0024] The metal nitride (B) preferably contains at least one metal element selected from the group consisting of Zn, Al, Ga, In, Ge, Sn, Li, Na, Mg, Ca, Sr, Ba, and La.
[0025] Examples of metal nitrides (B) include Zn3N2, AlN, GaN, InN, Ge3N4, ZnGeN2, ZnSnN2, Li3N, Na3N, Mg3N2, Ca3N2, Sr3N2, Ba3N2, and LaN.
[0026] The metal nitride (B) may contain a Zn-containing metal nitride (B-1). Examples of metal oxides (B-1) include Zn3N2, ZnGeN2, ZnSnN2, etc., with Zn3N2 being preferred.
[0027] Metal nitride (B) may further contain metal nitride (B-2) other than metal nitride (B-1). When metal nitride (B-1) is Zn3N2, metal nitride (B-2) may be at least one selected from the group consisting of AlN, GaN, InN, Ge3N4, ZnGeN2, ZnSnN2, Li3N, Na3N, Mg3N2, Ca3N2, Sr3N2, Ba3N2, and LaN, and preferably at least one selected from the group consisting of AlN, GaN, InN, Ge3N4, ZnGeN2, and ZnSnN2.
[0028] The metal nitride (B) may be a compound (B') containing a metal element, a nitrogen atom, and a halogen atom. Examples of compound (B') include Zn2NX, Li4NX, Mg2NX, etc. (X represents a halogen atom, preferably Cl, Br, or I). Compound (B') may be, for example, Zn2NX.
[0029] The metal halide (C) preferably contains at least one metallic element selected from the group consisting of Zn, Al, Ga, In, Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, and La.
[0030] Examples of metal halides (C) include ZnX2, AlX3, GaX3, InX3, LiX, NaX, KX, RbX, CsX, MgX2, CaX2, SrX2, BaX2, LaX3, etc. (X represents a halogen atom, preferably Cl, Br, or I).
[0031] The metallic element of the metal halide (C) is preferably the same as at least one of the metallic elements of the metal oxide (A) and the metal nitride (B), and more preferably the same as at least one of the metallic elements of the metal nitride (B).
[0032] The metal halide (C) is preferably a compound that melts at the heating temperature of the reaction step. That is, the melting point of the metal halide (C) is preferably below the heating temperature of the reaction step.
[0033] The melting point of metal halide (C) may be, for example, 1000°C or less, preferably 850°C or less, and more preferably 500°C or less. A low melting point of metal halide (C) is not particularly problematic, and it may be a liquid at room temperature, but from the viewpoint of excellent storage properties and workability, it may be, for example, 50°C or higher, and may be 100°C or higher.
[0034] In the reaction process, the content of metal oxide (A) and metal nitride (B) in the mixture may be adjusted as appropriate according to the desired composition of the oxynitride.
[0035] The content of metal nitride (B) in the mixture may be such that, for example, the ratio (N1 / N0) of the amount of nitrogen atoms N1 in metal nitride (B) to the theoretical amount N0 of nitrogen atoms required to form the target oxynitride is between 1.0 and 5.0. The above ratio (N1 / N0) is, for example, 1.0 or more, and may be 1.1 or more. Also, the above ratio (N1 / N0) is, for example, 5.0 or less, and may be 4.0 or less, 3.0 or less, 2.0 or less, or 1.5 or less. The above theoretical value N0 can be said to be, for example, the theoretical amount of nitrogen atoms stoichiometrically required to form the metal nitride (i) constituting the oxynitride when the oxynitride is a solid solution of metal nitride (i) and metal oxide (ii).
[0036] In the reaction step, the content of metal halide (C) in the mixture may be such that, for example, the molar ratio (M3 / (M1+M2)) of the amount of metal elements in metal halide (C) to the total amount of metal elements in metal oxide (A) and metal nitride (B) (M1+M2) is 0.05 to 20. The above molar ratio (M3 / (M1+M2)) is, for example, 0.05 or more, and may be 0.1 or more, 0.2 or more, or 0.3 or more. Alternatively, the above molar ratio (M3 / (M1+M2)) may be, for example, 20 or less, and may be 15 or less, 10 or less, 5 or less, 3 or less, or 1 or less.
[0037] In this embodiment, the method for mixing the metal oxide (A), metal nitride (B), and metal halide (C) is not particularly limited, but it is preferable to mix them under an inert gas atmosphere (for example, under a nitrogen atmosphere) in order to avoid oxidation of the metal nitride (B) and moisture absorption of the metal halide (C).
[0038] In the reaction step, a mixture of metal oxide (A), metal nitride (B), and metal halide (C) is heated in a closed system. The method for forming the closed system is not particularly limited and can be, for example, a vacuum sealed tube or an autoclave.
[0039] In the reaction process, it is desirable that water and oxygen be sufficiently excluded within the closed system. From this viewpoint, heating within the closed system is preferably carried out under reduced pressure, under vacuum, or under an inert gas atmosphere, and more preferably under reduced pressure or under vacuum. Examples of inert gases include nitrogen, argon, and helium.
[0040] The heating temperature in the reaction step may be, for example, 600°C or higher, preferably 700°C or higher, and more preferably 750°C or higher. Higher heating temperatures tend to yield oxynitrides with higher crystallinity. Alternatively, the heating temperature in the reaction step may be, for example, 1000°C or lower, and may be 900°C or lower, or 850°C or lower. This tends to reduce problems such as contamination by impurities due to thermal decomposition of the oxynitride, rupture of the closed system due to increased internal pressure, and contamination by impurities due to chemical corrosion of the closed system.
[0041] The heating time in the reaction step may be, for example, 1 hour or more, preferably 4 hours or more, and more preferably 10 hours or more. This tends to make it easier to obtain oxynitrides with higher crystallinity. There is no particular upper limit to the heating time in the reaction step, but from the viewpoint of reducing problems such as contamination by impurities due to thermal decomposition of the oxynitride, decrease in crystallinity, and contamination by impurities due to chemical corrosion of the closed system, it may be, for example, 168 hours or less, 96 hours or less, or 48 hours or less.
[0042] The reaction step may be, for example, a step of heating a mixture of a metal oxide (A) Ga2O3, a metal nitride (B) Zn3N2, and a metal halide (C) in a closed system to obtain an oxynitride (GaN:ZnO), which is a solid solution of GaN and ZnO. In this step, the metal halide is preferably ZnX2 (where X represents a halogen atom, preferably Cl, Br, or I).
[0043] The reaction step may also involve heating a mixture of metal oxides (A) GeO2 and ZnO, metal nitrides (B) Zn3N2, and a metal halide (C) in a closed system to obtain an oxynitride (ZnGeN2:ZnO), which is a solid solution of ZnGeN2 and ZnO. In this step, the metal halide is preferably ZnX2 (where X represents a halogen atom, preferably Cl, Br, or I).
[0044] The mixture in the reaction step may further contain other components besides metal oxides (A), metal nitrides (B), and metal halides (C).
[0045] Other components include, for example, dopants that dope the oxynitride. Examples of dopants include Li2O, MgO, and Al2O3.
[0046] The dopant content in the mixture may be such that, for example, the molar ratio (M4 / (M1+M2)) of the amount of metal elements in the dopant to the total amount of metal elements in the metal oxide (A) and metal nitride (B) (M1+M2) is 0.1 or less. The above molar ratio (M4 / (M1+M2)) is, for example, 0.1 or less, and may be 0.05 or less or 0.01 or less.
[0047] Other components include elemental elements that promote grain growth of oxynitrides. Examples of elemental elements include Zn and I2.
[0048] The amount of elemental metals in the mixture may be such that, for example, the molar ratio (M5 / (M1+M2)) of the amount of elemental metals (M5) to the total amount of metal elements (M1+M2) contained in the metal oxide (A) and metal nitride (B) is 0.5 or less. The above molar ratio (M5 / (M1+M2)) is, for example, 0.5 or less, and may be 0.1 or less or 0.01 or less.
[0049] The manufacturing method of this embodiment may further include a calcination step in which the oxynitride obtained in the reaction step is calcined. The calcination step reduces the defect density of the oxynitride, which tends to make the oxynitride more suitable as a photocatalyst.
[0050] The firing process includes firing under an oxygen-containing atmosphere (hereinafter also referred to as firing (1)) and firing under an ammonia-containing atmosphere (hereinafter also referred to as firing (2)). In the firing process, either firing (1) or firing (2) may be performed, or both may be performed. When both firing (1) and firing (2) are performed, the order of performance is not particularly limited; it may be firing (1) followed by firing (2), or firing (2) followed by firing (1).
[0051] Furthermore, firing in an inert gas atmosphere (hereinafter referred to as firing (3)) is also an option in the firing process. In the firing process, firing (3) may be performed alone, or it may be performed in combination with either firing (1) or firing (2), or both. In this case, the order of performance is not particularly limited.
[0052] The firing process (1) may be, for example, firing under atmospheric pressure.
[0053] The firing temperature for firing (1) may be, for example, 400°C or higher, preferably 500°C or higher, and more preferably 550°C or higher. This allows the above-mentioned effects of firing to be more pronounced. Alternatively, the firing temperature for firing (1) may be, for example, 800°C or lower, preferably 700°C or lower, and more preferably 600°C or lower. This suppresses the deterioration of function due to the decomposition of the oxynitride, and tends to make the oxynitride more suitable as a photocatalyst.
[0054] The firing time for firing (1) may be, for example, 1 minute or more, preferably 10 minutes or more, and more preferably 30 minutes or more. This allows the above-mentioned effects of firing to be more pronounced. Alternatively, the firing time for firing (1) may be, for example, 5 hours or less, preferably 3 hours or less, and more preferably 2 hours or less. This suppresses the deterioration of function due to the decomposition of the oxynitride, and tends to make the oxynitride more suitable as a photocatalyst.
[0055] Calcination (2) may be, for example, calcination under an ammonia gas stream. Alternatively, calcination (2) may be calcination under an ammonia gas stream diluted with an inert gas. Examples of inert gases include nitrogen, argon, and helium.
[0056] In calcination (2), at least one compound selected from the group consisting of ZnO, ZnX2, AlX3, GaX3, InX3, LiX, NaX, KX, RbX, CsX, MgX2, CaX2, SrX2, BaX2, and LaX3 (where X represents a halogen atom, preferably Cl, Br, or I) may be added to the oxynitride. The amount of compound added may be, for example, 200 parts by mass or less, 100 parts by mass or less, or 50 parts by mass or less per 100 parts by mass of the oxynitride.
[0057] The firing temperature for firing (2) may be, for example, 500°C or higher, preferably 600°C or higher, and more preferably 700°C or higher. This allows the above-mentioned effects of firing to be more pronounced. Alternatively, the firing temperature for firing (2) may be, for example, 1000°C or lower, preferably 900°C or lower, and more preferably 850°C or lower. This suppresses the decrease in the amount of metal oxide solid-solved in the oxynitride due to the volatilization of metal oxides.
[0058] The firing time for firing (2) may be, for example, 1 minute or more, preferably 10 minutes or more, and more preferably 30 minutes or more. This allows the above-mentioned effects of firing to be more pronounced. Alternatively, the firing time for firing (2) may be, for example, 5 hours or less, preferably 3 hours or less, and more preferably 2 hours or less. This suppresses the deterioration of function due to the decomposition of the oxynitride, and tends to make the oxynitride more suitable as a photocatalyst.
[0059] The firing (3) is performed under an inert gas atmosphere (e.g., nitrogen, argon, helium, etc.), and may also be performed in an inert gas stream.
[0060] The firing temperature for firing (3) may be, for example, 400°C or higher, preferably 500°C or higher, and more preferably 550°C or higher. This allows the above-mentioned effects of firing to be more pronounced. Alternatively, the firing temperature for firing (3) may be, for example, 800°C or lower, preferably 700°C or lower, and more preferably 600°C or lower. This suppresses the deterioration of function due to the decomposition of the oxynitride, and tends to make the oxynitride more suitable as a photocatalyst.
[0061] The firing time for firing (3) may be, for example, 1 minute or more, preferably 10 minutes or more, and more preferably 30 minutes or more. This allows the above-mentioned effects of firing to be more pronounced. Alternatively, the firing time for firing (3) may be, for example, 5 hours or less, preferably 3 hours or less, and more preferably 2 hours or less. This suppresses the deterioration of function due to the decomposition of the oxynitride, and tends to make the oxynitride more suitable as a photocatalyst.
[0062] The manufacturing method of this embodiment may further include an acid treatment step in which an acidic solution is brought into contact with the oxynitride after the reaction step.
[0063] The acid treatment process allows for the dissolution and removal of impurities such as oxides from the oxynitride. This makes the supporting process, in which oxidation reaction co-catalysts and reduction reaction co-catalysts are supported on the oxynitride to obtain a photocatalyst, more effective.
[0064] The acidic solution used in the acid treatment process may be a solution in which an acidic component is dissolved in a solvent. Examples of acidic components include mineral acids such as nitric acid, hydrochloric acid, and sulfuric acid, and organic acids such as formic acid, acetic acid, citric acid, benzenesulfonic acid, and poly(4-styrenesulfonic acid). Examples of solvents include water.
[0065] The oxynitride produced by the manufacturing method of this embodiment can be suitably used as a photosemiconductor in photocatalysts (particularly photocatalysts for photohydrolysis reactions). Furthermore, the oxynitride produced by the manufacturing method of this embodiment can also be suitably used in applications such as phosphors, pigments, and catalyst supports.
[0066] (Method for manufacturing photocatalysts) The method for producing the photocatalyst of this embodiment includes a supporting step in which an oxidation reaction co-catalyst and a reduction reaction co-catalyst are supported on an oxynitride produced by the above-described method to obtain a photocatalyst.
[0067] As an oxidation reaction co-catalyst, any known oxidation reaction co-catalyst used in photocatalysts can be used without any particular limitations.
[0068] The oxidation reaction co-catalyst may be a catalyst containing a metal element such as Mn, Fe, Co, Ni, Ru, Rh, or Ir. Alternatively, the oxidation reaction co-catalyst may be a single metal, an oxide, or an oxyhydroxide. Specific examples of oxidation reaction co-catalysts include MnO, MnO2, Mn2O3, Mn3O4, FeOOH, CoO, Co3O4, CoOOH, RuO2, and IrO2.
[0069] The amount of oxidation reaction co-catalyst supported is not particularly limited and may be appropriately selected depending on the application and performance of the photocatalyst. The amount of oxidation reaction co-catalyst supported may be determined by the amount of metal element contained in the oxidation reaction co-catalyst (hereinafter also referred to as the metal support amount). The metal support amount of the oxidation reaction co-catalyst may be, for example, 0.001 parts by mass or more per 100 parts by mass of oxynitride. Preferably, it is 0.01 parts by mass or more, more preferably 0.05 parts by mass or more. Alternatively, the metal support amount of the oxidation reaction co-catalyst may be, for example, 5 parts by mass or less per 100 parts by mass of oxynitride, preferably 1 part by mass or less, more preferably 0.5 parts by mass or less.
[0070] Two or more oxidation reaction co-catalysts may be used in combination. In this embodiment, in particular, by using a first catalyst containing a metal element selected from the group consisting of Ir, Ru, Mn, and Fe (preferably Ir) and a second catalyst containing Co as oxidation reaction co-catalysts in combination, a photocatalyst with superior hydrogen production ability tends to be obtained.
[0071] As a reduction reaction co-catalyst, any known reduction reaction co-catalyst used in photocatalysts can be used without any particular limitations.
[0072] Examples of cocatalysts for reduction reactions include Pt, Pd, Rh, Ru, Ir, Ni, Cu, Au, Fe, NiO, RuO2, IrO2, Rh2O3, Rh-Cr composite oxides, core / shell type Rh / Cr2O3, and Pt / Cr2O3.
[0073] The amount of reduction reaction co-catalyst supported is not particularly limited and may be appropriately selected depending on the application and performance of the photocatalyst. The amount of reduction reaction co-catalyst supported may be determined by the amount of metal element contained in the reduction reaction co-catalyst (hereinafter also referred to as the metal support amount). The metal support amount of the reduction reaction co-catalyst may be, for example, 0.01 parts by mass or more per 100 parts by mass of oxynitride. Preferably, it is 0.05 parts by mass or more, more preferably 0.1 parts by mass or more. Alternatively, the metal support amount of the reduction reaction co-catalyst may be, for example, 10 parts by mass or less per 100 parts by mass of oxynitride, preferably 5 parts by mass or less, more preferably 1 part by mass or less.
[0074] The method for supporting the oxidation reaction co-catalyst and reduction reaction co-catalyst is not particularly limited, and known support methods can be used without any particular restrictions. Examples of support methods include impregnation, photoelectrodeposition, microwave heating, hydrothermal, precipitation, adsorption, vapor deposition, sputtering, atomic layer deposition, and arc plasma.
[0075] (Methods for producing hydrogen (and oxygen)) The hydrogen production method of this embodiment includes a water splitting step in which a photocatalyst produced by the above-described production method is brought into contact with water to decompose the water. In the water splitting step, hydrogen is generated by the decomposition of water. In addition, oxygen may be further generated in the water splitting step by the decomposition of water. That is, the hydrogen production method of this embodiment can also be described as a method for producing oxygen, or a method for producing both hydrogen and oxygen.
[0076] In the water splitting process, when the photocatalyst is in contact with water, the photocatalyst receives light, generating oxygen on the oxidation reaction co-catalyst and hydrogen on the reduction reaction co-catalyst. The light that the photocatalyst receives can be natural light (sunlight) or artificial light.
[0077] In the water splitting process, the pH of the water may be adjusted by adding a pH adjusting agent. Examples of pH adjusting agents include acids, acidic compounds, bases, basic compounds, and salts thereof.
[0078] In the water splitting process, organic compounds may be added to the water. If organic compounds are present, they may be oxidized by the photocatalytic reaction, leading to a dehydrogenation reaction and the generation of hydrogen. In addition, the consumption of holes in the photocatalyst prevents excited electrons from recombining with holes, allowing the water reduction reaction to proceed more efficiently and tending to improve the hydrogen production rate.
[0079] Examples of organic compounds that can be used include alcohols such as methanol and ethanol; aldehydes such as formaldehyde and acetaldehyde; sugars such as glucose; and carboxylic acids such as ascorbic acid.
[0080] Although preferred embodiments of the present invention have been described above, the present invention is not limited to the above embodiments. [Examples]
[0081] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0082] (Example A-1) The following method was used to produce oxynitride (GaN:ZnO). (i) Synthesis of Zn3N2 2 g of Zn powder (High Purity Chemical Laboratory Co., Ltd., 99%) was weighed, placed on an alumina boat, and heated to 600°C at a heating rate of 10°C / min. Zn3N2 was synthesized by heating with an ammonia flow rate of 100 mL / min for 10 hours. (ii) reaction process Ga2O3 (High Purity Chemical Laboratory Co., Ltd., 99.99%), Zn3N2, and ZnI2 (Sigma-Aldrich, ≥98%) were weighed in a molar ratio of 1:1.1:2 (1.87g, 2.47g, and 6.38g), mixed, and a volume of approximately 100cm³ was prepared. 3 The mixture was transferred to a quartz tube. Weighing and mixing were performed in a nitrogen-purged glove box to prevent oxidation of Zn3N2 and moisture absorption of ZnI2. The quartz tube containing the mixture was vacuumed for 2 hours, then sealed with a burner to create a vacuum-sealed tube. The vacuum-sealed tube was heated in an electric furnace at a heating rate of 150°C / hour to 430°C, held for 2 hours, and then heated again at a heating rate of 150°C / hour to 850°C for 10 hours. After natural cooling to room temperature, the sealed tube was broken to obtain the oxynitride. (iii) Firing process One g of the oxynitride obtained in the reaction process was weighed into an alumina crucible and heated in air at a heating rate of 10°C / min to 600°C for 1 hour. The heated oxynitride was treated with a 0.5 M nitric acid aqueous solution, washed with water, and dried overnight.
[0083] (Comparative Example X-1) The oxynitrides were produced using the following method. Ga2O3 (High Purity Chemical Laboratory Co., Ltd., 99.99%) and ZnO (Kanto Chemical Co., Ltd., ≥99.5%) were weighed in molar quantities such that Zn / Ga = 2 (0.73g and 1.27g respectively), thoroughly mixed, placed on an alumina boat, and heated to 850°C at a heating rate of 10°C / min under a flow of ammonia at 250 mL / min for 15 hours. The product was transferred to an alumina crucible and heated to 600°C at a heating rate of 10°C / min in air for 1 hour to obtain oxynitride.
[0084] (Comparative Example X-2) The oxynitride was produced using the following method. Ga2O3 (High Purity Chemical Laboratory Co., Ltd., 99.99%) and ZnO (Kanto Chemical Co., Ltd., ≥99.5%) were weighed in a molar ratio of Zn / Ga=2 (0.73g and 1.27g respectively), thoroughly mixed, placed on an alumina boat, and heated to 950°C at a heating rate of 10°C / min under a flow of ammonia at 250 mL / min for 15 minutes. After heating, the sample was treated with a 0.5 M nitric acid aqueous solution, washed with water, and dried overnight to obtain oxynitride.
[0085] (Comparative Example X-3) The oxynitrides were produced using the following method. GaCl3 (Wako Pure Chemical Industries, 99.9%), ZnCl2 (Wako Pure Chemical Industries, ≥98%), and urea (Wako Pure Chemical Industries, 99%) were weighed in molar ratios of GaCl3:ZnCl2:urea = 1:1:1 (0.528g, 0.409g, and 0.180g). 10 mL of pure water was added, and the mixture was stirred while maintaining a temperature of 70°C or higher to completely evaporate the water and dry the mixture. The product was placed on an alumina boat and heated to 500°C at a rate of 10°C / min under an ammonia flow of 250 mL / min for 8 hours to obtain oxynitrides.
[0086] (Comparative Example X-4) The oxynitride was produced in the same manner as in Comparative Example X-3, except that the heating temperature under ammonia flow was set to 800°C.
[0087] <Analysis and evaluation of oxynitrides> The oxynitrides obtained in Example A-1, Comparative Example X-1, Comparative Example X-2, Comparative Example X-3, and Comparative Example X-4 were analyzed using a desktop X-ray diffractometer (XRD, MiniFlex, Rigaku Corporation, CuKα rays), a diffuse reflectance spectrophotometer (V-670, JASCO Corporation), a desktop scanning electron microscope with energy-dispersive X-ray analyzer (SEM-EDX, PhenonPharos, Thermo Fisher Scientific K.K.), a field emission scanning electron microscope (FE-SEM, Hitachi High-Tech Corporation, SU-8000), an energy-dispersive X-ray fluorescence analyzer (XRF, EDX-800HS2, Shimadzu Corporation), an inductively coupled plasma emission spectrometer (ICP-OES, ICPS-8100, Shimadzu Corporation), and an oxygen / nitrogen analyzer (EMGA-620W, Horiba Ltd.).
[0088] Furthermore, the crystallinity of the oxynitride was evaluated from the crystallite size obtained by applying the following Scherrer formula to the diffraction peak appearing at 33° to 38° in the powder X-ray diffraction pattern (corresponding to 101 diffraction). τ = Kλ / βcosθ (In the formula, τ is a crystallite, K (=0.89) is the shape factor, λ is the X-ray wavelength, β is the peak full width at half maximum, and θ is the Bragg angle.)
[0089] Figure 1(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Example A-1, Comparative Example X-1, Comparative Example X-2, Comparative Example X-3, and Comparative Example X-4, and Figure 1(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Example A-1, Comparative Example X-1, Comparative Example X-2, Comparative Example X-3, and Comparative Example X-4.
[0090] As shown in Figure 1(a), the oxynitride of Example A-1 showed a peak shift towards ZnO compared to the oxynitrides of Comparative Examples X-1 and X-2, confirming a higher solid solubility of ZnO. Furthermore, as shown in Figure 1(b), the oxynitride of Example A-1 showed a shift in the absorption rise to higher wavelengths compared to the oxynitrides of Comparative Examples X-1 and X-2, confirming that it is capable of visible light absorption over a wider range.
[0091] Furthermore, as shown in Figure 1(a), the oxynitride of Example A-1 had a similar peak angle and a similar amount of ZnO solid solution compared to the oxynitrides of Comparative Examples X-3 and X-4, but it was confirmed that the peak was sharper and it had higher crystallinity.
[0092] Furthermore, elemental analysis using SEM-EDX, XRF, and ICP-OES confirmed that the Zn / (Zn+Ga) molar ratio of the oxynitride of Example A-1 was 0.57. The Zn / (Zn+Ga) molar ratios of the oxynitrides of Comparative Examples X-1, X-2, X-3, and X-4 were 0.23, 0.35, 0.50, and 0.32, respectively.
[0093] Furthermore, the crystallite sizes determined by the above method were 39 nm for the oxynitride of Example A-1, 51 nm for the oxynitride of Comparative Example X-1, 31 nm for the oxynitride of Comparative Example X-2, 12 nm for the oxynitride of Comparative Example X-3, and 12 nm for the oxynitride of Comparative Example X-4.
[0094] As described above, in Comparative Examples X-1 to X-4, oxynitrides were synthesized by thermal nitriding under ammonia flow. However, with this manufacturing method, ZnO in the oxynitride is easily discharged from the system, making it difficult to achieve both high ZnO solid solubility and high crystallinity. In contrast, in Example A-1, an oxynitride with high ZnO solid solubility and high crystallinity was obtained.
[0095] (Example A-2) (ii) The oxynitride was obtained in the same manner as in Example A-1, except that the heating temperature in the reaction step was changed from 850°C to 700°C.
[0096] (Example A-3) (ii) The oxynitride was obtained in the same manner as in Example A-1, except that the heating time in the reaction step was changed from 10 hours to 50 hours.
[0097] <Analysis and evaluation of oxynitrides> The oxynitrides obtained in Examples A-1, A-2, and A-3 were analyzed and evaluated in the same manner as described above. Figure 2(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples A-1, A-2, and A-3, and Figure 2(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Examples A-1, A-2, and A-3. Figure 3(a) shows the FE-SEM image of the oxynitride obtained in Example A-1, and Figure 3(b) shows the FE-SEM image of the oxynitride obtained in Example A-2.
[0098] As shown in Figure 1(a), the oxynitrides of Examples A-1 and A-2 showed XRD peaks at similar angles, suggesting that the amount of ZnO dissolved was similar. On the other hand, the oxynitride of Example A-3 had a shift in its XRD peak to a higher angle compared to the oxynitrides of Examples A-1 and A-2, suggesting a lower amount of ZnO dissolved. Furthermore, comparing the peaks, the peak of Example A-1 was the sharpest, followed by the peak of Example A-2, suggesting that the oxynitride of Example A-1 had the highest crystallinity, followed by the oxynitride of Example A-2, and that the oxynitride of Example A-3 had lower crystallinity compared to these.
[0099] The Zn / (Zn+Ga) molar ratio in the oxynitride of Example A-1 was 0.57, the Zn / (Zn+Ga) molar ratio in the oxynitride of Example A-2 was 0.56, and the Zn / (Zn+Ga) molar ratio in the oxynitride of Example A-3 was 0.41.
[0100] Furthermore, the crystallite size of the oxynitride in Example A-1 was 39 nm, the crystallite size of the oxynitride in Example A-2 was 31 nm, and the crystallite size of the oxynitride in Example A-3 was 27 nm.
[0101] (Example B-1) A photocatalyst was produced by supporting a co-catalyst on the oxynitride of Example A-1 using the following loading process. 0.15 g of oxynitride and 15 mL of pure water were placed in a 30 mL microwave irradiation device container. An aqueous solution of Na3IrCl6·xH2O with an Ir concentration of 5.18 mg / mL was added. The suspension was thoroughly dispersed by sonication, and then rapidly heated to 150°C in a microwave irradiation device, where it was maintained for 10 minutes. During heating, the mixture was continuously stirred at 1000 rpm using a stirring bar. After the reaction, the solution was washed with water and recovered by filtration. Next, Rh was supported by photoelectrodeposition. A methanol aqueous solution was used as the reaction solution, and a Na3RhCl6·nH2O aqueous solution was used as the Rh source. After Rh support, the material was recovered by filtration to obtain the photocatalyst. In the photocatalyst, the amount of Ir supported (in terms of metallic elements) per 100 parts by mass of oxynitride was 0.1 parts by mass, and the amount of Rh (in terms of metallic elements) supported was 1.0 part by mass.
[0102] (Example B-2) The photocatalyst was manufactured in the same manner as in Example B-1, except that the oxynitride from Example A-2 was used as the oxynitride.
[0103] <Evaluation of hydrogen generation activity> The hydrogen generation activity of the photocatalysts obtained in Examples B-1 and B-2 was evaluated by the following method. The photocatalyst was dispersed in a 10 vol% methanol aqueous solution using ultrasound for approximately 10-20 seconds. The reaction system was thoroughly degassed, argon was introduced at 10 kPa, and visible light from a 300 W xenon lamp was irradiated. The amount of hydrogen produced was measured every hour using a gas chromatograph with a thermal conductivity detector connected to the reaction system. Figure 4 shows the evaluation results of the hydrogen generation activity of the photocatalysts obtained in Examples B-1 and B-2.
[0104] As shown in Figure 4, the photocatalysts of Examples B-1 and B-2 were confirmed to function as photocatalysts when exposed to visible light. Furthermore, the photocatalyst of Example B-1 showed higher hydrogen production activity compared to the photocatalyst of Example B-2.
[0105] (Example C-1) (ii) The oxynitride was produced in the same manner as in Example A-2, except that the molar ratio of Ga2O3, Zn3N2, and ZnI2 was changed to 1:1.1:1 in the reaction step. The photocatalyst was also produced in the same manner as in Example B-1, except that the obtained oxynitride was used.
[0106] (Comparative Example X-5) (ii) The oxynitride was produced in the same manner as in Example A-2, except that ZnI2 was not used in the reaction step. The photocatalyst was obtained in the same manner as in Example B-1, except that the obtained product was used.
[0107] <Analysis and evaluation of oxynitrides> The oxynitrides obtained in Example A-2, Example C-1, and Comparative Example X-5 were analyzed and evaluated in the same manner as described above. Figure 5(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Example A-2, Example C-1, and Comparative Example X-5, and Figure 5(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Example A-2, Example C-1, and Comparative Example X-5.
[0108] As shown in Figure 5(a), Comparative Example X-5 showed a peak similar to that of the composite oxide (ZnGa2O4), suggesting the formation of the composite oxide. On the other hand, the oxynitride of Example C-1 showed an XRD peak at a similar angle to that of the oxynitride of Example A-2, confirming the formation of an oxynitride with a similar amount of ZnO solid solution. In addition, a peak similar to that of the composite oxide (ZnGa2O4) was observed in Example C-1, suggesting that the composite oxide (ZnGa2O4) was formed as a byproduct. Furthermore, as shown in Figure 5(b), in Comparative Example X-5, the absorption rise was on the shorter wavelength side compared to Examples A-2 and C-1, suggesting that no oxynitride was formed and a composite oxide was formed.
[0109] Furthermore, as shown in Figure 5(a), a comparison of Example A-2 and Example C-1 reveals that the peak of Example A-2 is sharper, suggesting that the oxynitride of Example A-2 has higher crystallinity.
[0110] The Zn / (Zn+Ga) molar ratio in the oxynitride of Example A-2 was 0.56, and the Zn / (Zn+Ga) molar ratio in the oxynitride of Example C-1 was 0.49.
[0111] Furthermore, the crystallite size of the oxynitride in Example A-2 was 31 nm, and the crystallite size of the oxynitride in Example C-1 was 24 nm.
[0112] <Evaluation of hydrogen generation activity> The hydrogen generation activity of the photocatalysts obtained in Example B-2, Example C-1, and Comparative Example X-5 was evaluated using the method described above. Figure 6 shows the evaluation of the hydrogen generation activity of the photocatalysts obtained in Example B-2, Example C-1, and Comparative Example X-5.
[0113] As shown in Figure 6, the photocatalysts in Examples B-2 and C-1 exhibited superior hydrogen generation activity compared to the photocatalyst in Comparative Example X-5.
[0114] (Example D-1) (ii) The oxynitride was produced in the same manner as in Example A-1, except that ZnI2 in the reaction step was changed to ZnI2 and ZnCl2 (molar ratio 1:1).
[0115] <Analysis and evaluation of oxynitrides> The oxynitrides obtained in Examples A-1 and D-1 were analyzed and evaluated in the same manner as described above. Figure 7(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples A-1 and D-1, and Figure 7(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Examples A-1 and D-1. Figure 8(a) shows the FE-SEM image of the oxynitride obtained in Example A-1, and Figure 8(b) shows the FE-SEM image of the oxynitride obtained in Example D-1.
[0116] As shown in Figure 7(a), the oxynitride of Example D-1 showed a similar peak to that of the oxynitride of Example A-1, confirming that it was an oxynitride with a similar ZnO solid volume. Furthermore, the oxynitride of Example D-1 was found to have a narrower peak width and higher crystallinity compared to the oxynitride of Example A-1.
[0117] The Zn / (Zn+Ga) molar ratio in the oxynitride of Example A-1 was 0.57, and the Zn / (Zn+Ga) molar ratio in the oxynitride of Example D-1 was 0.56.
[0118] Furthermore, the crystallite size of the oxynitride in Example A-1 was 39 nm, and the crystallite size of the oxynitride in Example D-1 was 48 nm.
[0119] Furthermore, as shown in Figures 8(a) and 8(b), it was confirmed that the oxynitride of Example D-1 had a larger particle size than the oxynitride of Example A-1. This is thought to be because in Example D-1, particle growth was promoted by using a mixture of ZnCl2 and ZnI2, which have a lower melting point than ZnI2, as the metal halide.
[0120] (Example E-1) (iii) The oxynitride was produced in the same manner as in Example A-1, except that the calcination process was changed to the process described in (iv) below. (iv) Firing process 1 g of the oxynitride obtained in reaction step (ii) was weighed into an alumina crucible and heated in air at a heating rate of 10°C / min to 600°C for 1 hour. The heated oxynitride was treated with a 0.5 M aqueous nitric acid solution, washed with water, and dried overnight. The oxynitride was then transferred to an alumina boat and heated to 800°C at a heating rate of 10°C / min under a flow of 50 mL / min of ammonia and heated for 1 hour.
[0121] Next, a photocatalyst was produced using the obtained oxynitride by the following method. 0.15 g of oxynitride and 15 mL of pure water were placed in a 30 mL microwave irradiation device container. An aqueous solution of Na3IrCl6·xH2O with an Ir concentration of 5.18 mg / mL was added. The suspension was thoroughly dispersed by sonication, and then rapidly heated to 150°C in a microwave irradiation device, where it was maintained for 10 minutes. During heating, the mixture was continuously stirred at 1000 rpm using a stirring bar. After the reaction, the solution was washed with water and recovered by filtration. Next, Rh was supported by photoelectrodeposition. A methanol aqueous solution was used as the reaction solution, and a Na3RhCl6·nH2O aqueous solution was used as the Rh source. After Rh support, it was recovered by filtration, and then Cr2O3 was supported by photoelectrodeposition to obtain a photocatalyst. Pure water was used as the reaction solution, and K2CrO4 was used as the Cr source. In the photocatalyst, the amount of Ir supported (in terms of metallic elements) was 0.1 parts by mass, the amount of Rh supported was 0.1 parts by mass, and the amount of Cr supported (in terms of metallic elements) was 0.1 parts by mass per 100 parts by mass of oxynitride.
[0122] (Example E-2) (iv) In the calcination process (2), the oxynitride was produced in the same manner as in Example E-1, except that the heating temperature under ammonia flow was changed from 800°C to 850°C. Furthermore, a photocatalyst was produced using the obtained oxynitride in the same manner as in Example E-1.
[0123] <Analysis and evaluation of oxynitrides> The oxynitrides obtained in Examples E-1 and E-2 were analyzed and evaluated in the same manner as described above. Figure 9(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples E-1 and E-2, and Figure 9(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Examples E-1 and E-2.
[0124] As shown in Figure 9(a), calcination under ammonia flow caused the XRD peak to shift towards the high-angle side (GaN side), suggesting that zinc oxide in the oxynitride was reduced and volatilized. The amount of this shift was larger in Example E-2, which was calcined at a higher temperature. The crystallite sizes of the oxynitrides in Examples E-1 and E-2, determined from 10¹ diffraction, were 28 nm and 28 nm, respectively, which were smaller than the crystallite size (39 nm) of the oxynitride in Example A-1, which did not undergo calcination step (2). The Zn / (Zn+Ga) (molar ratio) of the oxynitrides in Examples E-1 and E-2 were determined to be 0.45 and 0.41, respectively, which were lower than the Zn / (Zn+Ga) (0.57) of the oxynitride in Example A-1.
[0125] Figure 9(b) shows that the onset of light absorption shifts to shorter wavelengths, corresponding to the shift in the XRD peak and the decrease in Zn / (Zn+Ga). Although calcination under ammonia flow shifted the onset of light absorption to shorter wavelengths, the oxynitride obtained had a longer onset of light absorption compared to Comparative Example X-1.
[0126] <Evaluation of water splitting activity> The water-splitting activity of the photocatalysts obtained in Examples E-1 and E-2 was evaluated using the following method. The photocatalyst was dispersed in pure water using ultrasound for approximately 10-20 seconds. The reaction system was thoroughly degassed, argon was introduced at 10 kPa, and visible light from a 300 W xenon lamp was irradiated. The amount of hydrogen and oxygen produced was measured every hour using a gas chromatograph with a thermal conductivity detector connected to the reaction system. Figure 10 shows the evaluation results of the water-splitting activity of the photocatalysts obtained in Examples E-1 and E-2.
[0127] As shown in Figure 10, the photocatalysts obtained in Examples E-1 and E-2 were confirmed to function as photocatalysts with visible light water-splitting activity. It should be noted that synthesis of GaN:ZnO with an absorption edge beyond 500 nm and exhibiting visible light water-splitting activity is difficult by ammonia thermal nitriding (e.g., Comparative Examples X-1 to X-4), and there have been no reported examples to date.
[0128] (Example F-1) (iii) The oxynitride was produced in the same manner as in Example A-1, except that the firing process was changed to the process described in (v) below. (v) Firing process 1 g of the oxynitride obtained in reaction step (ii) was transferred to an alumina boat and heated to 850°C at a heating rate of 10°C / min for 1 hour under a gas flow of a mixed gas of 10 mL / min of ammonia and 40 mL / min of nitrogen. Then, the oxynitride was weighed into an alumina crucible and heated to 600°C at a heating rate of 10°C / min in air for 1 hour. The heated oxynitride was treated with a 0.5 M aqueous nitric acid solution, washed with water, and dried overnight to obtain the oxynitride.
[0129] (Example F-2) (v) The oxynitride was produced in the same manner as in Example F-1, except that the calcination process was changed from "under a flow of a mixed gas of 10 mL / min of ammonia and 40 mL / min of nitrogen" to "under a flow of a mixed gas of 25 mL / min of ammonia and 25 mL / min of nitrogen".
[0130] (Example F-3) (v) The oxynitride was produced in the same manner as in Example F-1, except that the calcination process was changed from "under a mixed gas flow of 10 mL / min of ammonia and 40 mL / min of nitrogen" to "under a flow of 50 mL / min of ammonia".
[0131] <Analysis and evaluation of oxynitrides> The oxynitrides obtained in Examples F-1, F-2, and F-3 were analyzed and evaluated in the same manner as described above. Figure 11(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples A-1, F-1, F-2, and F-3, and Figure 11(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Examples A-1, F-1, F-2, and F-3.
[0132] As shown in Figure 11(a), the higher the ammonia concentration during the calcination process, the more the XRD peak shifts towards the higher angle side (GaN side), suggesting that zinc oxide in the oxynitride tends to be reduced and volatilized more easily during the calcination process.
[0133] The Zn / (Zn+Ga) molar ratio in the oxynitride of Example A-1 was 0.57, the Zn / (Zn+Ga) molar ratio in the oxynitride of Example F-1 was 0.53, the Zn / (Zn+Ga) molar ratio in the oxynitride of Example F-2 was 0.48, and the Zn / (Zn+Ga) molar ratio in the oxynitride of Example F-3 was 0.48.
[0134] Furthermore, the crystallite size of the oxynitride in Example A-1 was 39 nm, the crystallite size of the oxynitride in Example F-1 was 30 nm, the crystallite size of the oxynitride in Example F-2 was 28 nm, and the crystallite size of the oxynitride in Example F-3 was 27 nm.
[0135] (Example G-1) (v) In the calcination process, 0.25 g of ZnO (Kanto Chemical Co., Ltd., ≥99.0%) was added to 1.00 g of oxynitride and mixed, except that the oxynitride was produced in the same manner as in Example F-1.
[0136] (Example G-2) (v) In the calcination process, 0.50 g of ZnO (Kanto Chemical Co., Ltd., ≥99.0%) was added to 1.00 g of oxynitride and mixed, except that the oxynitride was produced in the same manner as in Example F-1.
[0137] (Example G-3) (v) In the calcination process, 1.00 g of ZnO (Kanto Chemical Co., Ltd., ≥99.0%) was added to 1.00 g of oxynitride and mixed, except that the oxynitride was produced in the same manner as in Example F-1.
[0138] <Analysis and evaluation of oxynitrides> The oxynitrides obtained in Examples G-1, G-2, and G-3 were analyzed and evaluated in the same manner as described above. Figure 12(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples F-1, G-1, G-2, and G-3, and Figure 12(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Examples F-1, G-1, G-2, and G-3.
[0139] As shown in Figure 12(a), the addition of ZnO suppressed the broadening of the XRD peak.
[0140] The Zn / (Zn+Ga) molar ratio in the oxynitride of Example F-1 was 0.53, the Zn / (Zn+Ga) molar ratio in the oxynitride of Example G-1 was 0.53, the Zn / (Zn+Ga) molar ratio in the oxynitride of Example G-2 was 0.53, and the Zn / (Zn+Ga) molar ratio in the oxynitride of Example G-3 was 0.55.
[0141] Furthermore, the crystallite size of the oxynitride in Example F-1 was 30 nm, the crystallite size of the oxynitride in Example G-1 was 36 nm, the crystallite size of the oxynitride in Example G-2 was 36 nm, and the crystallite size of the oxynitride in Example G-3 was 37 nm.
[0142] (Example H-1) The following method was used to produce oxynitride (ZnGeN2:ZnO). (i) Synthesis of Zn3N2 2 g of Zn powder (High Purity Chemical Laboratory Co., Ltd., 99%) was weighed, placed on an alumina boat, and heated to 600°C at a heating rate of 10°C / min. Zn3N2 was synthesized by heating with an ammonia flow rate of 100 mL / min for 10 hours. (ii) reaction process ZnO (Kanto Chemical Co., Ltd., ≥99.0%), GeO2 (High Purity Chemical Laboratory Co., Ltd., 99.99%), Zn3N2, and ZnCl2 (Kanto Chemical Co., Ltd., ≥98%) were weighed in a molar ratio of 1:1:1.1:2 (0.326g, 0.419g, 0.986g, and 1.090g respectively), mixed, and a volume of approximately 9.5 cm³ was produced.3 The mixture was transferred to a quartz tube. Weighing and mixing were performed in a nitrogen-purged glove box to prevent oxidation of Zn3N2 and moisture absorption of ZnCl2. The quartz tube containing the mixture was vacuumed for 2 hours, then sealed with a burner to create a vacuum-sealed tube. The vacuum-sealed tube was heated in an electric furnace at a heating rate of 150°C / hour to 430°C, held for 2 hours, and then heated again at a heating rate of 150°C / hour to 750°C for 20 hours. After natural cooling to room temperature, the sealed tube was broken to obtain the oxynitride. (iii) Firing process 0.3 g of the oxynitride obtained in the reaction step was weighed into an alumina boat and heated to 850°C at a heating rate of 10°C / min under a flow of ammonia at 20 mL / min for 1 hour. Then, it was transferred to an alumina crucible and heated to 600°C at a heating rate of 10°C / min in air for 1 hour. The heated oxynitride was treated with a 0.15 M aqueous nitric acid solution, washed with water, and dried overnight.
[0143] (Example H-2) In reaction step (ii), the heating time at 750°C was changed to 10 hours, but the oxynitride (ZnGeN2:ZnO) was produced in the same manner as in Example H-1.
[0144] (Example H-3) In reaction step (ii), the heating time at 750°C was changed to 40 hours, but the oxynitride (ZnGeN2:ZnO) was produced in the same manner as in Example H-1.
[0145] (Example H-4) In reaction step (ii), the heating time at 750°C was changed to 80 hours, but the oxynitride (ZnGeN2:ZnO) was produced in the same manner as in Example H-1.
[0146] (Comparative Example Y-1) The oxynitrides were produced using the following method. (i) reaction process ZnO (Kanto Chemical Co., Ltd., ≥99.0%), GeO2 (High Purity Chemical Laboratory Co., Ltd., 99.99%), Zn (High Purity Chemical Laboratory Co., Ltd., 99%), and NH4Cl (Kanto Chemical Co., Ltd., ≥99.5%) were weighed in a molar ratio of 1:1:3:2 (0.366g, 0.471g, 0.883g, and 0.481g respectively), mixed, and a volume of approximately 9.5 cm³ was produced. 3 The mixture was transferred to a quartz tube. Weighing and mixing were performed in a nitrogen-purged glove box to prevent oxidation of Zn and moisture absorption of NH4Cl. The quartz tube containing the mixture was vacuum-sealed for 2 hours, then sealed with a burner to create a vacuum-sealed tube. The vacuum-sealed tube was heated in an electric furnace at a heating rate of 150°C / hour to 430°C, held for 2 hours, and then heated again at a heating rate of 150°C / hour to 750°C for 20 hours. After natural cooling to room temperature, the sealed tube was broken and the contents were recovered. The contents were washed with water and dried to obtain oxynitride. (ii) Firing process 0.3 g of the oxynitride obtained in the reaction step was weighed into an alumina boat and heated to 850°C at a heating rate of 10°C / min under a flow of ammonia at 20 mL / min for 1 hour. Then, it was transferred to an alumina crucible and heated to 600°C at a heating rate of 10°C / min in air for 1 hour. The heated oxynitride was treated with a 0.15 M aqueous nitric acid solution, washed with water, and dried overnight.
[0147] (Comparative Example Y-2) The oxynitrides were produced using the following method. ZnO (Kanto Chemical Co., Ltd., ≥99.0%) and GeO2 (Kanto Chemical Co., Ltd., 99.99%) were weighed in a molar ratio of 5:1 (1.59 g and 0.41 g respectively), mixed, packed into quartz wool, and loaded into a tubular furnace. The sample was heated to 850°C at a heating rate of 10°C / min under an ammonia flow of 20 mL / min for 15 hours to obtain oxynitrides.
[0148] <Analysis and evaluation of oxynitrides> The oxynitrides obtained in Examples H-1, H-2, H-3, H-4, Comparative Example Y-1, and Comparative Example Y-2 were analyzed and evaluated in the same manner as described above.
[0149] Figure 13(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Example H-1, Comparative Example Y-1, and Comparative Example Y-2, and Figure 13(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Example H-1, Comparative Example Y-1, and Comparative Example Y-2.
[0150] As shown in Figure 13(a), the oxynitride of Example H-1 shows a peak shift towards ZnO compared to the oxynitride of Comparative Example Y-2, confirming a higher solid solubility of ZnO. Furthermore, as shown in Figure 13(b), the absorption rise of the oxynitride of Example H-1 is shifted to higher wavelengths compared to the oxynitride of Comparative Example Y-2, confirming that it is capable of visible light absorption over a wider range.
[0151] Furthermore, as shown in Figure 13(a), it was confirmed that the oxynitride of Comparative Example Y-1 contained metallic Ge as an impurity. Also, as shown in Figure 13(b), the oxynitride of Comparative Example Y-1 showed continuous absorption on the long-wavelength side. The continuous light absorption in the long-wavelength region is thought to be due to the metallic Ge impurity in the oxynitride, and this result also suggests the presence of metallic Ge. It is thought that the metallic Ge was generated by the reduction of GeO2 or the reductive decomposition of the oxynitride during or after its formation, caused by hydrogen generated from the decomposition of NH4Cl.
[0152] Figure 14(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples H-1, H-2, H-3, and H-4, and Figure 14(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Examples H-1, H-2, H-3, H-4, and Comparative Example Y-2.
[0153] As shown in Figure 14(a), the oxynitrides of Examples H-1, H-2, H-3, and H-4 had XRD peaks at similar angles and were confirmed to be oxynitrides with similar amounts of ZnO solid solution. Furthermore, the XRD peaks of the oxynitrides of Examples H-1 to H-3 were sharper compared to the oxynitride of Example H-4, suggesting that oxynitrides with superior crystallinity can be obtained by setting an appropriate heating time.
[0154] (Example I-1) A photocatalyst was produced by supporting a co-catalyst on the oxynitride of Example H-1 using the following loading process. 0.11 g of oxynitride was placed in pure water and thoroughly dispersed by ultrasonic irradiation for about 60 seconds. Then, aqueous solutions of Na3RhCl6 and Cr(NO3)3 were added. The volume of the suspension was adjusted to about 3 mL. After evaporating the suspension to dryness on a water bath, it was collected and transferred to a magnetic crucible, and heated in air at a rate of 10 °C / min to 350 °C for 1 hour. In the photocatalyst, the amount of Rh supported (in terms of metallic elements) was 3.0 parts by mass and the amount of Cr supported (in terms of metallic elements) was 0.2 parts by mass per 100 parts by mass of oxynitride.
[0155] (Example I-2) The photocatalyst was manufactured using the same method as in Example I-1, except that the oxynitride from Example H-3 was used.
[0156] (Example I-3) The photocatalyst was manufactured using the same method as in Example I-1, except that the oxynitride from Example H-4 was used.
[0157] <Evaluation of hydrogen generation activity> The hydrogen generation activity of the photocatalysts obtained in Examples I-1, I-2, and I-3 was evaluated using the method described above. As a result, the hydrogen production rate of the photocatalyst in Example I-1 was 0.2 μmol / h, the hydrogen production rate of the photocatalyst in Example I-2 was 1.5 μmol / h, and the hydrogen production rate of the photocatalyst in Example I-3 was 6.1 μmol / h. These results confirm that the photocatalysts in Examples I-1 to I-3 function as photocatalysts when exposed to visible light.
[0158] (Example J-1) The following method was used to produce oxynitride (GaN:ZnO). (i) Synthesis of Zn3N2 2 g of Zn powder (High Purity Chemical Laboratory Co., Ltd., 99%) was weighed, placed on an alumina boat, and heated to 600°C at a heating rate of 10°C / min. Zn3N2 was synthesized by heating with an ammonia flow rate of 100 mL / min for 10 hours. (ii) reaction process Ga2O3 (High Purity Chemical Laboratory Co., Ltd., 99.99%), Zn3N2, and ZnBr2 (Tokyo Chemical Industries, Ltd., ≥98.0%) were weighed (0.68g, 0.986g, and 2.480g) in a molar ratio of 1:1.27:3.19, mixed, and filled to a volume of approximately 100cm³. 3 The mixture was transferred to a quartz tube. Weighing and mixing were performed in a nitrogen-purged glove box to prevent oxidation of Zn3N2 and moisture absorption of ZnBr2. The quartz tube containing the mixture was vacuumed for 2 hours, then sealed with a burner to create a vacuum-sealed tube. The vacuum-sealed tube was heated in an electric furnace at a heating rate of 150°C / hour to 430°C, held for 2 hours, and then heated again at a heating rate of 150°C / hour to 700°C for 10 hours. After natural cooling to room temperature, the sealed tube was broken to obtain the oxynitride. (iii) Firing process 1 g of the oxynitride obtained in reaction step (ii) was transferred to an alumina boat and heated to 850°C at a heating rate of 10°C / min under a flow of ammonia at 50 mL / min for 1 hour. Then, the oxynitride was weighed into an alumina crucible and heated to 600°C at a heating rate of 10°C / min in air for 1 hour. The heated oxynitride was treated with a 0.5 M aqueous nitric acid solution, washed with water, and dried overnight to obtain the oxynitride.
[0159] (Example J-2) Except for changing the heating temperature in reaction step (ii) from 700°C to 800°C, oxynitride (GaN:ZnO) was produced in the same manner as in Example J-1.
[0160] <Analysis and evaluation of oxynitrides> The oxynitrides obtained in Examples A-1, J-1, and J-2 were analyzed and evaluated in the same manner as described above. Figure 15(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples A-1, J-1, and J-2, and Figure 15(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Examples A-1, J-1, and J-2.
[0161] As shown in Figure 15(a), the oxynitrides of Examples J-1 and J-2 showed similar peaks to those of the oxynitride of Example A-1, and the peaks were on the lower angle side (ZnO side), confirming that they were oxynitrides with a similar or slightly larger ZnO solid volume. Furthermore, as shown in Figure 15(b), it was confirmed that the oxynitrides of Examples J-1 and J-2 absorbed visible light to a similar or slightly longer wavelength range than the oxynitride of Example A-1.
[0162] Furthermore, the crystallite size of the oxynitride in Example J-1 was 26 nm, and the crystallite size of the oxynitride in Example J-2 was 38 nm.
[0163] (Example K-1) The following methods were used to produce oxynitrides (GaN:ZnO) and photocatalysts. (i) Production of GaN:ZnO 2.5 g of Zn powder (high-purity chemical, 99%) was weighed, placed on an alumina boat, and heated to 600°C at a heating rate of 10°C / min. Zn3N2 was synthesized by heating with an ammonia flow rate of 300 mL / min for 4 hours. Next, weigh out Ga2O3, Zn3N2, and Zn12 in a molar ratio of 1:1.1:5 (1.4996g, 1.9725g, and 12.769g respectively), mix them, and fill to a volume of approximately 80cm³. 3The mixture was transferred to a quartz tube. Weighing and mixing were performed in a nitrogen-purged glove box to prevent oxidation of Zn3N2 and moisture absorption of Zn12. The quartz tube containing the mixture was vacuum-sealed for 2 hours, then sealed with a burner to create a vacuum-sealed tube. The vacuum-sealed tube was heated in an electric furnace at 150°C / hour to 430°C, held for 2 hours, then heated again at 150°C / hour to 850°C, held for 10 hours, and then allowed to cool naturally to room temperature. After cooling to room temperature, the sealed tube was broken and the sample was removed. The sample was washed with pure water and then dried in a vacuum dryer. 0.5 g of the dried sample was weighed into an alumina boat and heated at 850°C for 1 hour under a flow of nitrogen-diluted NH3 (NH3 10 mL / min + N2 40 mL / min). The sample was then transferred to an alumina crucible and heated in air at a rate of 10°C / min to 600°C for 1 hour. After heating, it was treated with 0.5 M dilute nitric acid, washed with water, filtered, and dried overnight to obtain oxynitride (GaN:ZnO). (ii) Production of photocatalysts Iridium oxide (IrO2) was supported on oxynitride (GaN:ZnO) by microwave irradiation as an oxidation reaction co-catalyst. Heating was carried out at 150°C for 10 minutes while stirring at 1000 rpm. After that, the sample powder was washed with distilled water and recovered by filtration. Next, Rh was supported on the sample powder as a reduction reaction co-catalyst by photoelectrodeposition in methanol aqueous solution. Na3RhCl6 aqueous solution was used as the Rh source. Furthermore, in order to form a Cr2O3 / Rh core shell, Cr2O3 was supported by photoelectrodeposition in distilled water to obtain a photocatalyst. K2CrO4 aqueous solution was used as the Cr source. In the photocatalyst, the amount of Ir (in terms of metal element) supported was 0.1 parts by mass, the amount of Rh (in terms of metal element) supported was 0.1 parts by mass, and the amount of Cr (in terms of metal element) supported was 0.1 parts by mass per 100 parts by mass of oxynitride.
[0164] (Example K-2) To the photocatalyst obtained in Example K-1, cobalt oxide (CoO) was added as an oxidation reaction co-catalyst. xThe oxynitride was supported by photoelectrodeposition. First, an aqueous Co(NO3)2 solution was added to the photocatalyst obtained in Example K-1 so that the amount of Co supported was 0.1 parts by mass per 100 parts by mass of oxynitride, and the reaction system was thoroughly degassed. Then, argon was introduced at 10 kPa, and the photocatalyst of Example K-2 was obtained by irradiating with visible light from a 300 W xenon lamp.
[0165] <Evaluation of water splitting activity> The photocatalysts obtained in Examples K-1 and K-2 were evaluated for their water-splitting activity using the following method. The photocatalyst was dispersed in pure water using ultrasound for approximately 10-20 seconds. The reaction system was thoroughly degassed, argon was introduced at 10 kPa, and visible light from a 300 W xenon lamp was irradiated. The hydrogen and oxygen production rates were measured using a gas chromatograph with a thermal conductivity detector connected to the reaction system. Figure 16 shows the evaluation results of the water-splitting activity of the photocatalysts obtained in Examples K-1 and K-2. The measurement results showed that the photocatalyst in Example K-1 produced hydrogen at a rate of 0.8 μmol / h and oxygen at a rate of 0.4 μmol / h. The photocatalyst in Example K-2 produced hydrogen at a rate of 1.5 μmol / h and oxygen at a rate of 0.5 μmol / h.
[0166] (Example L-1) The following methods were used to produce oxynitride (ZnGeN2:ZnO) and photocatalysts. (i) Production of ZnGeN2:ZnO 2 g of Zn powder (high-purity chemical, 99%) was weighed, placed on an alumina boat, and heated to 600°C at a rate of 10°C / min. Zn3N2 was synthesized by heating with an ammonia flow rate of 100 mL / min for 10 hours. Next, weigh out ZnO, GeO2, Zn3N2, and ZnCl2 in a molar ratio of 1:1:1.1:2 (0.3256g, 0.4185g, 0.9863g, and 1.090g respectively), mix them, and fill the container with a volume of approximately 9.5 cm³. 3The mixture was transferred to a quartz tube. Weighing and mixing were performed in a nitrogen-purged glove box to prevent oxidation of Zn3N2 and moisture absorption of ZnCl2. The quartz tube containing the mixture was vacuumed for 2 hours, then sealed with a burner to create a vacuum-sealed tube. The vacuum-sealed tube was heated in an electric furnace at 150°C / hour to 430°C, held for 2 hours, then heated again at 150°C / hour to 750°C, held for 40 hours, and then allowed to cool naturally to room temperature. After cooling to room temperature, the sealed tube was broken and the sample was removed. Next, 0.3 g of the sample was weighed into an alumina boat and heated at 850°C for 1 hour under an ammonia flow of 20 mL / min. Then, the sample was transferred to an alumina crucible and heated in air at a rate of 10°C / min to 600°C for 1 hour. After heating, it was treated with 0.15 M dilute nitric acid, washed with water, filtered, and dried overnight to obtain oxynitride (ZnGeN2:ZnO). (ii) Production of photocatalysts Iridium oxide (IrO2) was supported on an oxynitride (ZnGeN2:ZnO) as an oxidation reaction co-catalyst by microwave heating. Specifically, 0.11 g of oxynitride and distilled water were placed in a container and thoroughly dispersed by ultrasonic irradiation for about 60 seconds. An aqueous solution of sodium hexachloroiridium(IV) hexahydrate (Na2IrCl6·6H2O) was then added to obtain a suspension. The amounts of pure water and aqueous solution were adjusted so that the volume of the suspension was about 15 mL, and the amount of Ir supported in terms of metallic element was 0.1 parts by mass per 100 parts by mass of oxynitride. Next, the temperature was raised to 150°C by microwave irradiation and held for 10 minutes, then rapidly cooled to 70°C using an air compressor, and the sample was collected by suction filtration. Next, rhodium (Rh), a co-catalyst for the reduction reaction, was loaded onto the sample by photoelectrodeposition. Specifically, 0.1 g of the sample was weighed and suspended in 100 mL of 10 vol% methanol aqueous solution in a reaction vessel. Then, an aqueous solution of sodium hexachlororhodium(III) n-hydrate (Na3RhCl6·nH2O) was added to the reaction vessel so that the amount of Rh loaded, in terms of metallic elements, was 0.1 parts by mass per 100 parts by mass of oxynitride. The vessel was then connected to a closed circulation system and stirred with a stirrer. The system was thoroughly degassed, and argon gas was introduced to a pressure of approximately 10 kPa. By irradiating the reaction vessel with visible light (λ>420 nm) using a xenon lamp (300 W) adjusted to 20 A, a total reflection mirror, and a cutoff filter (L-42), a sample loaded with Rh was obtained. Next, chromium oxide (Cr2O3) was supported by photoelectrodeposition. Specifically, 0.1 g of the Rh-supported sample was weighed and dispersed in 100 mL of distilled water in a reaction vessel. Then, an aqueous solution of potassium chromate (K2CrO4) was added to the reaction vessel so that the amount of Cr supported in terms of metallic elements was 0.1 parts by mass per 100 parts by mass of oxynitride. The system was then connected to a closed circulation system and stirred with a stirrer. The system was thoroughly degassed, and argon gas was introduced to a pressure of approximately 10 kPa. By irradiating the reaction vessel with visible light (λ>420 nm) using a xenon lamp (300 W) adjusted to 20 A, a total reflection mirror, and a cutoff filter (L-42), the photocatalyst of Example L-1 was obtained.
[0167] (Example L-2) To the photocatalyst obtained in Example L-1, cobalt oxide (CoO) was added as an oxidation reaction co-catalyst. xThe photocatalyst was supported by photoelectrodeposition. Specifically, first, 0.1 g of the photocatalyst obtained in Example L-1 was weighed and dispersed in 100 mL of distilled water in a reaction vessel. Next, an aqueous solution of cobalt(II) nitrate hexahydrate (Co(NO3)2·6H2O) was added to the reaction vessel so that the amount of Co supported in terms of metallic elements was 0.1 parts by mass per 100 parts by mass of oxynitride, and the system was attached to a closed circulation system and stirred with a stirrer. The system was thoroughly degassed and argon gas was introduced to a pressure of approximately 10 kPa. The photocatalyst of Example L-2 was obtained by irradiating the reaction vessel with visible light (λ>420 nm) using a xenon lamp (300 W) adjusted to 20 A, a total reflection mirror, and a cutoff filter (L-42).
[0168] <Evaluation of water splitting activity> The water-splitting activity of the photocatalysts obtained in Example L-1 and Example L-2 was evaluated using the following method. In the reaction vessel, the photocatalyst was dispersed in distilled water using ultrasound for approximately 60 seconds. The reaction system was thoroughly degassed, and argon was introduced at 10 kPa. Visible light (λ>420 nm) was irradiated into the reaction vessel using a xenon lamp (300 W) adjusted to 20 A, a total reflection mirror, and a cutoff filter (L-42). The hydrogen and oxygen production rates were measured using a gas chromatograph with a thermal conductivity detector connected to the reaction system. Figure 17 shows the evaluation results of the water-splitting activity of the photocatalysts obtained in Examples L-1 and L-2. The measurement results showed that, on a 15-hour average, the photocatalyst in Example L-1 produced hydrogen at a rate of 0.29 μmol / h and oxygen at a rate of 0.14 μmol / h. The photocatalyst in Example L-2 produced hydrogen at a rate of 0.61 μmol / h and oxygen at a rate of 0.22 μmol / h.
[0169] <Example M-1> The following methods were used to produce metal halides and oxynitrides (ZnGeN2:ZnO). (i) Production of Zn2NCl 2 g of Zn powder (High Purity Chemicals, 99%) was weighed, placed in an alumina boat, heated to 600°C at a rate of 10°C / min, and heated for 10 hours at an ammonia flow rate of 100 mL / min to synthesize Zn3N2. Next, Zn3N2 and ZnCl2 were weighed (1.2328 g and 0.6814 g, respectively) to a molar ratio of 1.1:1, mixed, and transferred to a quartz tube with an internal volume of about 9.5 cm 3 . The weighing and mixing were performed in a nitrogen-purged glove box to prevent oxidation of Zn3N2 and moisture absorption of ZnCl2. The quartz tube containing the mixture was evacuated for 2 hours, then sealed with a burner to form a vacuum sealed tube. The vacuum sealed tube was heated in an electric furnace to 550°C at a rate of 10°C / min, held for 20 hours, and then naturally cooled to room temperature. After cooling to room temperature, the sealed tube was broken to take out Zn2NCl. (ii) Production of ZnGeN2:ZnO ZnO, GeO2, Zn2NCl, and ZnCl2 were weighed (0.1628 g, 0.2093 g, 0.7209 g, and 0.2720 g, respectively) to a molar ratio of 1:1:2:1, mixed, and transferred to a quartz tube with an internal volume of about 9.5 cm 3 . The weighing and mixing were performed in a nitrogen-purged glove box to prevent oxidation of Zn2NCl and moisture absorption of ZnCl2. The quartz tube containing the mixture was evacuated for 2 hours, then sealed with a burner to form a vacuum sealed tube. The vacuum sealed tube was heated in an electric furnace to 430°C at a rate of 150°C / hour, held for 2 hours, subsequently heated to 750°C at a rate of 150°C / hour, held for 10 hours, and then naturally cooled to room temperature. After cooling to room temperature, the sealed tube was broken to take out the sample.
[0170] <Example M-2> A metal halide nitride and an oxynitride (ZnGeN2:ZnO) were produced by the following method. (i) Production of Zn2NCl 2 g of Zn powder (High Purity Chemicals, 99%) was weighed, placed in an alumina boat, heated to 600°C at a rate of 10°C / min, and heated for 10 hours at an ammonia flow rate of 100 mL / min to synthesize Zn3N2. Next, Zn3N2 and ZnCl2 were weighed (1.2328 g and 0.6814 g, respectively) to a molar ratio of 1.1:1, mixed, and transferred to a quartz tube with an internal volume of about 9.5 cm3 The mixture was transferred to a quartz tube. Weighing and mixing were performed in a nitrogen-purged glove box to prevent oxidation of Zn3N2 and moisture absorption of ZnCl2. The quartz tube containing the mixture was vacuumed for 2 hours, then sealed with a burner to create a vacuum-sealed tube. The vacuum-sealed tube was heated in an electric furnace at a rate of 10°C / min to 550°C, held for 20 hours, and then allowed to cool naturally to room temperature. After cooling to room temperature, the sealed tube was broken open and Zn2NCl was extracted. (ii) Production of ZnGeN2:ZnO Weigh ZnO, GeO2, and Zn2NCl in a molar ratio of 1:1:2 (0.1628g, 0.2093g, and 0.7209g respectively), mix them, and fill a container with a volume of approximately 9.5 cm³. 3 The mixture was transferred to a quartz tube. Weighing and mixing were performed in a nitrogen-purged glove box to prevent oxidation of Zn2NCl. The quartz tube containing the mixture was vacuum-sealed for 2 hours, then sealed with a burner to create a vacuum-sealed tube. The vacuum-sealed tube was heated in an electric furnace at 150°C / hour to 430°C, held for 2 hours, then heated again at 150°C / hour to 750°C, held for 10 hours, and then allowed to cool naturally to room temperature. After cooling to room temperature, the sealed tube was broken and the sample was removed.
[0171] <Analysis and evaluation of oxynitrides> The oxynitrides obtained in Examples M-1 and M-2 were analyzed and evaluated in the same manner as described above. Figure 18(a) shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples M-1 and M-2, and Figure 18(b) shows the diffuse reflectance spectra of the oxynitrides obtained in Examples M-1 and M-2.
[0172] As shown in Figure 18(a), the oxynitrides of Example M-1 and Example M-2 had XRD peaks at similar angles, confirming that they were oxynitrides with similar ZnO solid solubility. Furthermore, the XRD peaks of the oxynitrides of Example M-1 and Example M-2 were lower angle (ZnO side) compared to the oxynitride of Comparative Example Y-2, confirming that they were oxynitrides with a larger ZnO solid capacity, and also confirming the presence of metallic Ge as an impurity. In addition, as shown in Figure 18(b), the oxynitrides of Example M-1 and Example M-2 were found to absorb visible light in a slightly longer wavelength range compared to the oxynitride of Comparative Example Y-2. Also, as shown in Figure 18(b), the oxynitrides of Example M-1 and Example M-2 showed continuous absorption in the longer wavelength range. This continuous light absorption in the longer wavelength range is thought to be due to the metallic Ge impurity in the oxynitride, and this result also confirms the presence of metallic Ge.
[0173] <Example N-1> The following methods were used to produce metal halides and oxynitrides (GaN:ZnO). (i) Production of Zn2NI 2.5 g of Zn powder (high-purity chemical, 99%) was weighed, placed on an alumina boat, and heated to 600°C at a rate of 10°C / min. Zn3N2 was synthesized by heating with an ammonia flow rate of 300 mL / min for 4 hours. Next, weigh out Zn3N2 and ZnI2 in a molar ratio of 1.1:1 (0.971g and 1.277g respectively), mix them, and fill the container with a volume of approximately 9.5 cm³. 3 The mixture was transferred to a quartz tube. Weighing and mixing were performed in a nitrogen-purged glove box to prevent oxidation of Zn3N2 and moisture absorption of ZnI2. The quartz tube containing the mixture was vacuumed for 2 hours, then sealed with a burner to create a vacuum-sealed tube. The vacuum-sealed tube was heated in an electric furnace at a rate of 10°C / min to 550°C, held for 20 hours, and then allowed to cool naturally to room temperature. After cooling to room temperature, the sealed tube was broken open to extract Zn2NI. (ii) Production of GaN:ZnO Ga2O3 and Zn2NI were weighed in a molar ratio of 1:2.2 (0.206g and 0.834g respectively), mixed, and the contents were filled to a volume of approximately 9.5 cm³. 3The mixture was transferred to a quartz tube. Weighing and mixing were performed in a nitrogen-purged glove box to prevent oxidation and moisture absorption of Zn2NI. The quartz tube containing the mixture was vacuumed for 2 hours, then sealed with a burner to create a vacuum-sealed tube. The vacuum-sealed tube was heated in an electric furnace at 150°C / hour to 430°C, held for 2 hours, then heated again at 150°C / hour to 850°C, held for 10 hours, and then allowed to cool naturally to room temperature. After cooling to room temperature, the sealed tube was broken and the sample was removed. The sample was treated with a 0.5 M nitric acid aqueous solution, washed with water, and dried overnight to obtain oxynitride.
[0174] <Example N-2> (i) Production of Zn2NI 2.5 g of Zn powder (high-purity chemical, 99%) was weighed, placed on an alumina boat, and heated to 600°C at a rate of 10°C / min. Zn3N2 was synthesized by heating with an ammonia flow rate of 300 mL / min for 4 hours. Next, weigh out Zn3N2 and ZnI2 in a molar ratio of 1.1:1 (0.971g and 1.277g respectively), mix them, and fill the container with a volume of approximately 9.5 cm³. 3 The mixture was transferred to a quartz tube. Weighing and mixing were performed in a nitrogen-purged glove box to prevent oxidation of Zn3N2 and moisture absorption of ZnI2. The quartz tube containing the mixture was vacuumed for 2 hours, then sealed with a burner to create a vacuum-sealed tube. The vacuum-sealed tube was heated in an electric furnace at a rate of 10°C / min to 550°C, held for 20 hours, and then allowed to cool naturally to room temperature. After cooling to room temperature, the sealed tube was broken open to extract Zn2NI. (ii) Production of GaN:ZnO Ga2O3, Zn2NI, and ZnI2 were weighed in a molar ratio of 1:2.2:5 (0.375g, 1.301g, and 3.192g respectively), mixed, and the resulting volume was approximately 9.5cm³. 3The mixture was transferred to a quartz tube. Weighing and mixing were performed in a nitrogen-purged glove box to prevent oxidation and moisture absorption of Zn2NI. The quartz tube containing the mixture was vacuumed for 2 hours, then sealed with a burner to create a vacuum-sealed tube. The vacuum-sealed tube was heated in an electric furnace at 150°C / hour to 430°C, held for 2 hours, then heated again at 150°C / hour to 850°C, held for 10 hours, and then allowed to cool naturally to room temperature. After cooling to room temperature, the sealed tube was broken and the sample was removed. The sample was treated with a 0.5 M nitric acid aqueous solution, washed with water, and dried overnight to obtain oxynitride.
[0175] <Analysis and evaluation of oxynitrides> The oxynitrides obtained in Examples N-1 and N-2 were analyzed and evaluated in the same manner as described above. Figure 19 shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples N-1 and N-2.
[0176] As shown in Figure 19, the oxynitrides of Example N-1 and Example N-2 had XRD peaks at similar angles and were confirmed to be oxynitrides with similar ZnO solid solubility. Furthermore, the XRD peaks of the oxynitrides of Example N-1 and Example N-2 were lower angle (ZnO side) compared to the oxynitride of Comparative Example X-1, for example, indicating that they were oxynitrides with a larger ZnO solid capacity. In addition, the crystallite sizes of the oxynitrides of Example N-1 and Example N-2 were 41 nm and 38 nm, respectively, which were similar to the crystallite size of the oxynitride of Example A-1 (39 nm). This suggests that in the reaction process, Zn2NI functions as both a zinc source and a nitrogen source, similar to a mixture of Zn3N2 and ZnI2.
[0177] <Example O-1> 2.5 g of Zn powder (high-purity chemical, 99%) was weighed, placed on an alumina boat, and heated to 600°C at a heating rate of 10°C / min. Zn3N2 was synthesized by heating with an ammonia flow rate of 300 mL / min for 4 hours. Next, Ga2O3, Zn3N2, and Zn12 are weighed out as raw materials in a molar ratio of 1:1.1:5 (0.562g, 0.740g, and 4.788g respectively), mixed, and the resulting volume is approximately 80cm³. 3The mixture was transferred to a quartz tube. Weighing and mixing were performed in a nitrogen-purged glove box to prevent oxidation of Zn3N2 and moisture absorption of Zn12. The quartz tube containing the mixture was vacuum-sealed for 2 hours, then sealed with a burner to create a vacuum-sealed tube. The vacuum-sealed tube was heated in an electric furnace at 150°C / hour to 430°C, held for 2 hours, then heated again at 150°C / hour to 850°C, held for 10 hours, and then allowed to cool naturally to room temperature. After cooling to room temperature, the sealed tube was broken and the sample was removed. The sample was washed with pure water and then dried in a vacuum dryer.
[0178] <Example O-2> Except for weighing Ga2O3, Zn3N2, Zn12, and I2 as raw materials in a molar ratio of 1:1.1:5:0.1 (0.562g, 0.740g, 4.788g, and 0.039g respectively), oxynitride (GaN:ZnO) was obtained using the same procedure as in Example O-1.
[0179] <Example O-3> Except for weighing Ga2O3, Zn3N2, Zn12, and I2 as raw materials in a molar ratio of 1:1.1:5:0.2 (0.562g, 0.740g, 4.788g, and 0.076g respectively), oxynitride (GaN:ZnO) was obtained using the same procedure as in Example O-1.
[0180] <Analysis and evaluation of oxynitrides> The oxynitrides obtained in Examples O-1, O-2, and O-3 were analyzed and evaluated in the same manner as described above. Figure 20 shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples O-1, O-2, and O-3.
[0181] As shown in Figure 20, the oxynitrides of Examples O-1, O-2, and O-3 had XRD peaks at similar angles and were confirmed to have similar amounts of ZnO solid solution. Furthermore, the XRD peaks of the oxynitrides of Examples O-1, O-2, and O-3 were lower angle (towards ZnO) compared to the oxynitride of Comparative Example X-1, for example, indicating that they were oxynitrides with a larger ZnO solid capacity. In addition, the crystallite size of the oxynitride of Example O-1 was 36 nm, while the crystallite sizes of the oxynitrides of Examples O-2 and O-3 were 40 nm and 39 nm, respectively, confirming that the crystallinity of the oxynitrides could be improved by adding an appropriate amount of I2.
[0182] <Example O-4> Except for weighing Ga2O3, Zn3N2, and ZnCl2 as raw materials in a molar ratio of 1:1.1:5 (1,500 g, 1,973 g, and 5,455 g respectively), oxynitride (GaN:ZnO) was obtained using the same procedure as in Example O-1.
[0183] <Example O-5> The oxynitride (GaN:ZnO) was obtained using the same procedure as in Example O-1, except that Ga2O3, Zn3N2, ZnCl2, and I2 were weighed out in a molar ratio of 1:1.1:5:0.05 (0.562g, 0.740g, 2.045g, and 0.019g respectively).
[0184] <Example O-6> Except for weighing Ga2O3, Zn3N2, ZnCl2, and I2 as raw materials in a molar ratio of 1:1.1:5:0.1 (0.562g, 0.740g, 2.045g, and 0.038g respectively), oxynitride (GaN:ZnO) was obtained using the same procedure as in Example O-1.
[0185] <Example O-7> Except for weighing Ga2O3, Zn3N2, ZnCl2, and I2 as raw materials in a molar ratio of 1:1.1:5:0.2 (0.562g, 0.740g, 2.045g, and 0.076g respectively), oxynitride (GaN:ZnO) was obtained using the same procedure as in Example O-1.
[0186] <Analysis and evaluation of oxynitrides> The oxynitrides obtained in Examples O-4 to O-7 were analyzed and evaluated in the same manner as described above. Figure 21 shows the powder X-ray diffraction patterns of the oxynitrides obtained in Examples O-4 to O-7.
[0187] As shown in Figure 21, the oxynitrides of Examples O-4 to O-7 had XRD peaks at similar angles and were confirmed to have similar amounts of ZnO solid solution. Furthermore, the XRD peaks of the oxynitrides of Examples O-4 to O-7 were lower angle (towards ZnO) compared to the oxynitride of Comparative Example X-1, for example, indicating that they were oxynitrides with a larger ZnO solid capacity. In addition, the crystallite size of the oxynitride of Example O-4 was 46 nm, while the crystallite sizes of the oxynitrides of Examples O-5, O-6, and O-7 were 50 nm, 52 nm, and 50 nm, respectively, confirming that the crystallinity of the oxynitrides could be improved by adding an appropriate amount of I2.
Claims
1. The process includes a reaction step of heating a mixture of a metal oxide (A), a metal nitride (B), and a metal halide (C) in a closed system. The metal oxide (A) comprises a metal oxide (A-1) containing at least one metal element selected from the group consisting of Ga and Ge. The metal nitride (B) includes a metal nitride (B-1) containing Zn. A method for producing an oxynitride, wherein the metal halide (C) has the same metal element as at least one of the metal elements present in the metal oxide (A) and the metal nitride (B).
2. The manufacturing method according to claim 1, wherein the metal oxide (A) further comprises a metal oxide (A-2) containing Zn.
3. The aforementioned metal nitride (B-1) is Zn 2 The manufacturing method according to claim 1, wherein the material is NX (where X represents a halogen atom).
4. The manufacturing method according to claim 1, wherein the oxynitride is a solid solution of a metal nitride (i) and a metal oxide (ii).
5. The manufacturing method according to claim 4, wherein the metal oxide (ii) contains ZnO.
6. The manufacturing method according to claim 4, wherein the metal nitride (i) contains at least one metal element selected from the group consisting of Ga and Ge.
7. The manufacturing method according to claim 1, further comprising a calcination step of calcining the oxynitride obtained in the reaction step.
8. The manufacturing method according to claim 7, wherein the firing step includes firing in an oxygen-containing atmosphere.
9. The manufacturing method according to claim 7, wherein the firing step includes firing in an ammonia-containing atmosphere.
10. The manufacturing method according to claim 7, wherein the firing step includes firing under an inert gas atmosphere.
11. A method for producing a photocatalyst, comprising the step of supporting an oxidation reaction co-catalyst and a reduction reaction co-catalyst on an oxynitride produced by the manufacturing method described in any one of claims 1 to 10 to obtain a photocatalyst.
12. A method for producing hydrogen, comprising the step of contacting a photocatalyst produced by the manufacturing method described in claim 11 with water to decompose the water.
Citation Information
Patent Citations
Method for synthesizing GaN: ZnO solid solution photocatalyst
CN103878011A
Nitric oxide elastic stress luminescent material and preparation method thereof
CN112340712A
METHOD FOR MANUFACTURING PHOTOCATALYST OF COMPOSITE METAL OXYNITRIDE GaN-ZnO
JP2006116415A
Powder containing tantalum (v)-based oxynitride with perovskite structure and producing method of the same
JP2011093743A
Photocatalyst for water photolysis reaction and method for producing the same
JP2011173102A
